2014
DOI: 10.1007/s10633-014-9432-3
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potential-based acuity assessment: overestimation in amblyopia

Abstract: Both measurements of visual acuity with the VEP and FrACT were highly reproducible. However, as expected, in amblyopia, acuity can be markedly overestimated using the VEP. We attribute this to the use of repetitive stimulus patterns (checkerboards), which also lead to overestimation in psychophysical measures. The VEP-based objective assessment never underestimated visual acuity, but needs to be interpreted with appropriate caution in amblyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…This approach was used in the Freiburg laboratory for a decade with high testability, (i.e., a ''no result outcome'' occurs in only 5-10% of the cases); problems in amblyopia have been described [5,6], and the algorithm was successfully extended to very low acuities (& 2 LogMAR) [7]. The stimulation and recording system was also used in other laboratories and is available free of charge [8].…”
Section: Introductionmentioning
confidence: 99%
“…This approach was used in the Freiburg laboratory for a decade with high testability, (i.e., a ''no result outcome'' occurs in only 5-10% of the cases); problems in amblyopia have been described [5,6], and the algorithm was successfully extended to very low acuities (& 2 LogMAR) [7]. The stimulation and recording system was also used in other laboratories and is available free of charge [8].…”
Section: Introductionmentioning
confidence: 99%
“…Third, luminance artifacts, a danger in onset stimulus, can be more easily avoided. The medium contrast of 40% was also used in their other studies [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Effects Of Visual Stimulimentioning
confidence: 99%
“…One combines the independent parts into a system, called a combined system, such as the systems in previous studies [ 7 , 35 , 36 , 68 , 75 , 104 ]. The other is a dedicated system utilized to generate the visual stimulus, record the VEP, and define the acuity in VEP assessment with some necessary auxiliary equipment, such as the Enfant system (Neuroscientific Corp., Farmingdale, NY, USA) [ 61 , 62 , 63 , 80 , 82 , 85 , 93 , 94 , 95 , 108 ], the PowerDiva system developed by Norcia (Smith-Kettlewell Eye Research Institute, San Francisco, CA, USA) [ 13 , 14 , 17 , 52 , 75 , 79 , 83 , 99 , 109 , 110 , 111 ], the RETIsystem (Roland Consult Instrument GmBH, Wiesbaden, Germany) [ 69 , 71 , 72 , 77 , 112 ], and the Freiburg Evoked Potentials (EP2000) system developed by Bach (Medical Center, Freiburg University, Freiburg, Germany) [ 22 , 30 , 31 , 113 ]. Bach and Farmer [ 26 ] evaluated the implementation and outcome quality of the VEP acuity method on commercial equipment (Diagnosys Espion Profile and E3 electrophysiology systems) and found that VEP acuity agreed with subjective acuity to within ± 0.31 logMAR, indicating that this technique can be accessible to more users.…”
Section: Effects Of Signal Acquisition and Analysismentioning
confidence: 99%
See 2 more Smart Citations